THE INFLUENCE OF GENDER ON SPEAKING ANXIETY IN ENGLISH CLASSES AT POLITEKNIK NEGERI CILACAP: A MIXED-METHODS STUDY AND PEDAGOGICAL IMPLICATIONS - Annisa Romadloni; Laura Sari; Linda Perdana Wati (EGALITA, 2025)
Abstract Speaking anxiety serves as a significant barrier to oral proficiency in English for Specific Purposes (ESP) courses. Yet, the influence of gender on this affective factor within Indonesian vocational education remains underexplored. This mixed-methods study investigated speaking anxiety patterns at Politeknik Negeri Cilacap. Data were collected from 90 students (45 male, 45 female) using a modified FLCAS questionnaire,written reflections, and classroom observations, complemented by in-depth interviews with twelve selected participants. Although aggregate anxiety scores did not differ significantly between genders, item-level analysis revealed distinct differences. Female students reported significantly higher anxiety when called upon without preparation (cold calls), when fearing negative evaluation, and when speaking before the whole class. At the same time, both genders experienced comparable anxiety levels during formal presentations. Qualitative data confirmed that the fear of making mistakes, sensitivity to lecturer and peer judgment, and a lack of preparation time were the primary drivers of these patterns. Based on these findings, the research advocates for the implementation of gender-responsive scaffolding. Suggested pedagogical strategies include providing structured "think time" before spontaneous questions, utilizing tiered speaking activities that progress from pair discussions to plenary reporting, and cultivating an error-friendly classroom culture. This approach aims to mitigate specific anxiety triggers for female students while building an inclusive environment that prepares all ESP learners for authentic professional communication.  Keywords: Gender; Speaking Anxiety; English for Spesific Purposes; Vocational Education.Abstrak Kecemasan berbicara merupakan hambatan signifikan bagi kemahiran lisan dalam mata kuliah English for Specific Purposes (ESP), namun pengaruh gender terhadap faktor afektif ini dalam pendidikan vokasi di Indonesia masih jarang diteliti. Studi mixed-methods ini menginvestigasi pola kecemasan berbicara di Politeknik Negeri Cilacap. Data dikumpulkan dari 90 mahasiswa (45 laki-laki, 45 perempuan) menggunakan kuesioner FLCAS yang dimodifikasi, refleksi tertulis, dan observasi kelas, dilengkapi dengan wawancara mendalam terhadap dua belas mahasiswa terpilih. Meskipun skor kecemasan agregat tidak berbeda signifikan antar-gender, analisis tingkat butir mengungkapkan perbedaan nyata. Mahasiswa perempuan melaporkan kecemasan yang jauh lebih tinggi saat dipanggil tanpa persiapan (cold calls), saat takut akan evaluasi negatif, dan ketika berbicara di depan seluruh kelas, sementara kedua gender memiliki tingkat kecemasan yang setara dalam presentasi formal. Data kualitatif mengonfirmasi bahwa ketakutan membuat kesalahan, sensitivitas terhadap penilaian dosen dan teman sebaya, serta kurangnya waktu persiapan merupakan pemicu utama pola tersebut. Berdasarkan temuan ini, penelitian merekomendasikan penerapan scaffolding responsif gender. Strategi pedagogis yang disarankan meliputi pemberian "waktu berpikir" terstruktur sebelum pertanyaan spontan, aktivitas berbicara berjenjang dari diskusi pasangan ke pelaporan pleno, serta penciptaan budaya kelas yang ramah terhadap kesalahan. Pendekatan ini bertujuan untuk memitigasi pemicu kecemasan spesifik pada mahasiswa perempuan sekaligus membangun lingkungan inklusif yang mempersiapkan seluruh pembelajar ESP untuk komunikasi profesional yang autentik.  Kata Kunci: Gender; Kecemasa Berbicara; English For Spesific Purposes; Pendidikan Vokasi